Influência do período de início do exercício físico na remodelação ventricular após o infarto do miocárdio - Batista, Diego Fernando [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The aim of our study was to evaluate the influence of the period of early physical activity on remodeling after infarction in rats by analysis of morphological, functional, biochemical, cellular and interstitial heart. Wistar rats were used, males, between 200 - 250g were subjected to experimental infarction. After 48 hours of the procedure, the surviving animals were randomly allocated into three groups: group S (n = 24): group of infarcted animals, group P (n = 24): group of infarcted animals exercised early; Group T (n = 24) : groups of infarcted animals exercised later. After 3 months of followup was conducted morphological and functional study of the following methods: isolated heart, echocardiography, histology and morphometry. Biochemical analysis was performed by the area of myocytes, infarct size and percentage of collagen in the cardiac tissue were assessed by spectrophotometry oxidative stress and energy metabolism. Statistical analysis was performed by ANOVA one-way, the significance level was 5%. Morphological assessed by echocardiogram showed that the animals in the late exercised had lower septal wall thickness that the group P (S = 1.69 ± 0.28, P = 1.81 ± 0.34, T = 1 , 46 ± 0.22, p = 0.041) and lower diastolic areas (S = 105 ± 12, P = 96 ± 23, T = 87 ± 11, p = 0.010) and systolic (S = 76 ± 8, P = 69 ± 8, T = 62 ± 9, p = 0.012) than the group S. In relation to functional variables assessed by echocardiography, the T group had higher shortening velocity of the posterior wall (PWSV) (S = 24 ± 4, P = 28 ± 6, T = 29 ± 3, p = 0.050) and A'média wave (S = 2.37 (2.25 to 3.25), P = 2.7 (2.5 to 3.0), T = 3.5 (3.5-4.4); p = 0.040) of the wave A 'Septal (S = 2.50 (2.0 to 3.25) P = 2.5 (2.12 to 3.0), T = 4.0 (3.12 - 4.0), p = 0.019) except IVRT / RR (S = 50.2 ± 10.7, P = 66.0 ± 10.7, T = 61.3 ± 9.4, p = 0.018) the P animals showed an improvement compared to the animals in group T. There were no differences in infarct ...

O bjetivo do nosso estudo foi de avaliar a influência do período de início da atividade física sobre a remodelação após o infarto em ratos, por meio de análise de variáveis morfológicas, funcionais, bioquímicas, celulares e intersticiais cardíacas. Foram utilizados ratos wistar, machos, entre 200 – 250g foram submetidos ao infarto experimental. Após 48hs do procedimento, os animais sobreviventes foram alocados em três grupos aleatoriamente: grupo S (n=24): grupo de animais infartados; grupo P (n=24): grupo de animais infartados exercitados precocemente; grupo T(n=24): grupos de animais infartados exercitados tardiamente. Após 3 meses de acompanhamento foi realizado estudo morfológico e funcional pelos seguintes métodos: coração isolado, ecocardiograma, morfometria e histologia. O estudo bioquímico foi realizado pela área de miócitos, tamanho do infarto e porcentagem de colágeno do tecido cardíaco, por espectrofotometria foram avaliados estresse oxidativo e metabolismo energético. A análise estatística foi realizada pelo teste de ANOVA de uma via, O nível de significância adotado foi de 5%. Os resultados morfológicos avaliados pelo ecocardiograma mostram que os animais do grupo exercitado tardiamente apresentaram menor espessura da parede septal que o grupo P (S=1,69±0,28; P=1,81±0,34; T=1,46±0,22; p=0,041) e menores áreas diastólicas (S=105±12; P=96±23; T=87±11; p=0,010) e sistólicas (S=76±8; P=69±8; T=62±9; p=0,012) que o grupo S. Em relação às variáveis funcionais avaliadas pelo ecocardiograma, o grupo T apresentou maiores valores da velocidade de encurtamento da parede posterior (VEPP) (S=24±4; P=28±6; T=29±3; p=0,050) e da onda A’média (S=2,37(2,25-3,25); P=2,7(2,5-3,0); T=3,5(3,5-4,4); p=0,040) da onda A’ Septal (S=2,50(2,0-3,25); P=2,5(2,12-3,0); T=4,0(3,12- 4,0); p=0,019) exceto o TRIV/R-R (S=50,2±10,7; P=66,0±10,7; T=61,3±9,4; p=0,018) os animais P mostraram uma melhora em ...
Keywords: Exercícios físicos; Infarto do miocárdio; Rato como animal de laboratorio; Coração - Ventriculos; Myocardial infarction